Improving Outcome in Severe Myasthenia Gravis and Guillain–Barré Syndrome - Hawkes, Maximiliano A.; Wijdicks, Eelco F. M. (Seminars in Neurology, 2024)
When progressive and severe, myasthenia gravis and Guillain–Barré syndrome may have the potential for fatal and unfavorable clinical outcomes. Regardless of important differences in their clinical course, the development of weakness of oropharyngeal muscles and respiratory failure with requirement of mechanical ventilation is the main driver of poor prognosis in both conditions. The need for prolonged mechanical ventilation is particularly relevant because it immobilizes the patient and care becomes extraordinarily complex due to daily risks of systemic complications. Additionally, patients with myasthenia gravis often require long-term immunosuppressive treatments with associated toxicity and infectious risks. Unlike myasthenia gravis, the recovery period is prolonged in Guillain–Barré syndrome, but often favorable, even in the more severely affected patients. Outcome, for a large part, is determined by expert neurocritical care.
Keywords: myasthenia gravis; Guillain-Barre Syndrome; Outcomes; Prognosis; Neurocritical care